2019
DOI: 10.1186/s13024-019-0332-6
|View full text |Cite
|
Sign up to set email alerts
|

Impaired dopamine metabolism in Parkinson’s disease pathogenesis

Abstract: A full understanding of Parkinson’s Disease etiopathogenesis and of the causes of the preferential vulnerability of nigrostriatal dopaminergic neurons is still an unsolved puzzle. A multiple-hit hypothesis has been proposed, which may explain the convergence of familial, environmental and idiopathic forms of the disease. Among the various determinants of the degeneration of the neurons in Substantia Nigra pars compacta , in this review we will focus on the endotoxicity associated to dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
169
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(179 citation statements)
references
References 168 publications
(271 reference statements)
8
169
0
2
Order By: Relevance
“…The remaining challenge is still understanding why changes in various proteins with altered or uncertain physiological functions congregate to comparable pathologic phenotypes, which are also observed in idiopathic PD [ 214 ]. Conversely, familial, environmental, and idiopathic PD forms present some differences from both the histopathological and clinical perspectives [ 215 ].…”
Section: Neurotoxin-induced Experimental In Vivo Models Of Pdmentioning
confidence: 99%
“…The remaining challenge is still understanding why changes in various proteins with altered or uncertain physiological functions congregate to comparable pathologic phenotypes, which are also observed in idiopathic PD [ 214 ]. Conversely, familial, environmental, and idiopathic PD forms present some differences from both the histopathological and clinical perspectives [ 215 ].…”
Section: Neurotoxin-induced Experimental In Vivo Models Of Pdmentioning
confidence: 99%
“…The impaired DA metabolism causes oxidative stress (ROS), which in turn leads to PD pathogenesis (Masato et al, 2019). It was reported that abnormal activity of vesicular monoamine transporter 2 (VMAT2) leads to reduced vesicular DA storage and increased cytoplasmic DA which results in oxidative stress-induced degeneration of cell bodies (soma) and terminals (Caudle et al, 2007;Kariya et al, 2005;Mingazov and Ugryumov, 2019;Pifl et al, 2014).…”
Section: Glutathione Therapymentioning
confidence: 99%
“…Three members of the synuclein family, α-, β-and γ-synuclein, are involved in various important molecular processes in presynaptic terminals. Gain-of-toxic-function is believed to be the main mechanism of the involvement of these proteins, α-synuclein in particular, in pathogenesis of Parkinson's disease and certain other neurodegenerative diseases collectively known as synucleinopathies, but the loss-offunction can also be a factor contributing to synaptic dysfunction associated with these diseases [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%